2019
DOI: 10.1002/jcp.28007
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA Linc00339 promotes triple‐negative breast cancer progression through miR‐377‐3p/HOXC6 signaling pathway

Abstract: Recently, long noncoding RNAs (lncRNAs) have become the key gene regulators and prognostic biomarkers in various cancers. Through microarray data, Linc00339 was identified as a candidate oncogenic lncRNA. We compared the expression levels of Linc00339 in several breast cancer cell lines and normal mammary gland epithelial cell line. The effects of Linc00339 on tumor progression were examined both in vitro and in vivo. 3‐(4,5‐Dimethylthiazol‐2‐yl)‐2,5‐diphenyltetrazolium bromide assays were applied to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 64 publications
(76 reference statements)
1
54
0
Order By: Relevance
“…23 Previous studies have reported that LINC00339 is the sponge for miR-377-3p, miR-145, and miR-539-5p. [12][13][14] This work for the first time identified LINC00339 as the sponge for miR-1182. To date, knowledge about miR-1182 is poor.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…23 Previous studies have reported that LINC00339 is the sponge for miR-377-3p, miR-145, and miR-539-5p. [12][13][14] This work for the first time identified LINC00339 as the sponge for miR-1182. To date, knowledge about miR-1182 is poor.…”
Section: Discussionmentioning
confidence: 83%
“…21 Recently, several researchers have demonstrated that LINC00339 promotes proliferation, migration, and invasion of laryngeal squamous cell carcinoma and breast cancer. 13,14 Its role in HCC remains limitedly studied. We provided evidence that LINC00339 promotes HCC tumorigenesis and metastasis through the miR-1182/ SKA1 pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five of these molecules have been shown to play important roles in breast cancer. For example, Wang et al, (2019b) reported that overexpression of miR-377 correlates with better prognosis in triple-negative breast cancer. ADAMTS-5 may alter the cellular microenvironment, affecting the balance between protumor and antitumor effects (Fontanil et al, 2017).…”
Section: Modules In the Dysregulated Network Relate To The Survival Omentioning
confidence: 99%
“…Similarly, lncRNA TROJAN promoted the proliferation of TNBC cells by inducing ZMYND8 degradation 92 . LINC00339 regulated TNBC cell growth by promoting proliferation and inhibiting apoptosis via regulation of miR‐377‐3p/HOXC6 expression 93 . Moreover, there are also some non‐classical lncRNA‐involved mechanisms in the regulation of TNBC progression.…”
Section: Long Non‐coding Rnasmentioning
confidence: 99%